Chrysin promotes oral ulcer healing via modulating matrix metalloproteinases and vascular endothelial growth factor in rats - Abeer Salama; Rania Elgohary (Iranian Journal of Basic Medical Sciences)
Objective(s): Oral ulcers are a common inflammatory condition affecting the mucosal lining, often causing pain and discomfort. Chrysin is a natural flavonoid with well-documented anti-oxidant and anti-inflammatory properties. This study investigates the therapeutic effect of chrysin in an experimental model of acetic acid-induced oral ulcers in rats.Materials and Methods: To establish an oral ulcerative mucositis model, 50% acetic acid was administered to the labial fornix of the inferior incisors. Chrysin gel (1% and 2%) was applied to the oral mucosa of rats with aggravated oral ulcerative mucositis that had developed after seven days of acetic acid application.Results: Chrysin gel after 7 days reduced buccal ulcer and inhibited inflammation and degradation of collagen induced by acetic acid via suppression of MDA, TNF-α, NF-κβ, IL-6, and matrix metalloproteinases (MMP9) as well as stimulation of GSH and vascular endothelial growth factor (VEGF) enhancing healing effect. Histopathological results exhibited that chrysin alleviated the muscle bundle degeneration in the tongue and the acinar lining epithelium degeneration of submandibular salivary glands. Conclusion: Chrysin gel can be used as an oral gel via its anti-inflammatory activity and induction of VEGF. It can also be tested clinically in oral human ulcers.